Stocking pattern for anti-malarial medications among proprietary patent medicine vendors in Akinyele Local Government Area, Ibadan, Nigeria (2020)
Background: Policymakers have recognized that proprietary patent medicine vendors (PPMVs) can provide an opportunity for efective scaling up of artemisinin-based combination therapy (ACT) since they constitute a major source of malaria treatment in Nigeria. This study was designed to determine the stocking pattern for anti-malarial medications, knowledge of the recommended anti-malarial medicine among PPMVs in Akinyele Local Govern ment Area (LGA) of Oyo State, Nigeria and their perception on ways to improve PPMV adherence to stocking ACT medicines. Methods: A cross-sectional survey was conducted among 320 PPMVs using a mixed method of data collection. Survey respondents were consecutively selected as a complete listing of all the PPMVs was not available. A pretested interviewer-administered questionnaire was used to collect quantitative data and two focus group discussions (FGD) were conducted among PPMVs using a pretested FGD guide. Results: Most PPMVs stocked artemether-lumefantrine (90.9%), dihydroartemisinin-piperaquine (5.3%) and artesunate-amodiaquine (2.8%). Drugs contrary to the policy, which included sulfadoxine-pyrimethamine, chloroquine, quinine, halofantrine, artesunate, and artemether were stocked by 93.8, 22.8, 0.6, 1.3, 6.6, and 7.8% of the PPMVs, respectively. Most PPMVs (96.3%) had good knowledge of artemether-lumefantrine as the first-line treatment for malaria and 2.8% had good knowledge of artesunate-amodiaquine as the alternate treatment for malaria. The major factors infuencing stocking decision were government recommendations (41.3%) and consumer demand (40.30%). Conclusion: Stocking of artemisinin-based combinations was high among PPMVs, although they also stocked and dispensed other anti-malarial drugs and this has serious implications for drug resistance development. The PPMVs had considerable knowledge of the recommended treatment for uncomplicated malaria and stocking decisions were overwhelmingly driven by consumer demand. However, there is a need for more enlightenment on discontinuation of government-banned anti-malarial drugs.